A power equation for the sprint in speed skating - Koning, J. J. de; Groot, G. de; van Ingen Schenau, G. J. (Journal of Biomechanics, 1992)
An analysis of the start of the 500 m speed skating races during the 1988 Olympic Winter Games showed a remarkably high correlation between the acceleration of the skater in the first second of the sprint and the final time. In this study a power equation is used to explain this high coefficient of correlation. The performance in speed skating is determined by the capability of external power production by the speed skater. This power is necessary to overcome the air and ice friction and to increase the kinetic energy of the skater. Numerical values of the power dissipated to air and ice friction, both dependent on speed, are obtained from ice friction and wind tunnel experiments. Using aerobic and anaerobic power production as measured during supra maximal bibycle tests of international-level speed skaters, a model of the kinetics of power production is obtained. Simultation of power production and power dissipation yields values of speed and acceleration and, finally, the performance time of the sprint during speed skating. The mean split time at 100 m and the final time at 500 m in these races, derived from simulation, were 10.57 s and 37.82 s, respectively. The coefficient of correlation between the simulated 500 m times and the actual 500 m times was 0.90. From the results of this study it can be concluded that the distribution of the available anaerobic energy is an important factor in the short lasting events. Verf.-Referat